Network routers : simulation of congestion control - Lim, Beng Kwee. (2008)
In this project, we have developed both a TCP-Reno model and network model, to explore router scheduling mechanisms. We investigate the issues involved in the building of a TCP Reno source and a network model. The TCP Reno traffic source and a network model used in our simulation have been designed and implemented successfully. This thesis presents results of a series of simulations designed to study the performances and fairness of various network congestion control algorithms used in the router. We proposed a new algo-rithm which extends Deficit Round Robin algorithm in order to handle bursty traffic when the router has limited buffer space and to provide support for weighted flows (commonly used to provide QoS).